Burkina Faso : Seventh Review Under the Extended Credit Facility Arrangement and Request for a New Three-Year Extended Credit Facility Arrangement. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Burkina Faso's Seventh Review Under the Extended Credit Facility (ECF) Arrangement and Request for a new Three-Year ECF Arrangement. Economic activity in Burkina Faso continued to grow at a brisk pace in 2013. Program performance remains strong. Revenue performance remains on target, but is no longer overshooting targets as in recent years, while spending execution is below target. Almost all program targets were met, including on net domestic financing and the fiscal balance. All structural benchmarks slated for completion in June and September were also met. The IMF staff supports completion of the seventh review of the current ECF arrangement and the authorities' request for a new three-year ECF arrangement with access equivalent to 45 percent of quota.